Accelerated Aging of T-Cell Subsets Among ART-Naïve HIV-Infected Chinese Men Who have Sex with Men: A Case-Control Study - Li, Li; Li, Xing-Wang; Ma, Cheng-Jie; Wang, Ling-Hang; Yu, Feng-Ting; Yang, Si-Yuan; Song, Shu-Jing; Tang, Yun-Xia (Current HIV Research, 2022)
Background: Evidence of lymphopoiesis, exhaustion, and premature aging in Chinese patients with human immunodeficiency virus (HIV) is very limited. Objective: To assess biological aging and immune senescence in Chinese healthy controls (HC) and ART-naïve HIV-infected men who have sex with men (MSM). Methods: This case-control study was conducted in Beijing Ditan Hospital from March 2018 to June 2019. The percentages of naïve (TN), central memory (TCM), effector memory (TEM), and terminally differentiated memory (TemRA) subsets of CD4 and CD8 T cells were studied, along with markers of senescence (CD28-CD57+) and activation (HLA-DR+). Telomere length of naïve (CD45RA+) and memory (CD45RO+) CD8 T cells were quantified by real-time PCR. Results: A total of 26 HIV-infected and 20 age-matched HC MSM were included. Compared to the HC group, the CD4/CD8 ratio of the HIV-infected group was significantly reduced (0.30 vs. 1.70, P<0.001); significant differences emerged among all CD8 but not CD4 T cell subsets (all P<0.05). In the HIV-infected group, the percentages of senescent cells (CD28-CD57+) in TN, TCM, TEM, and TemRA subsets of CD8 T cells were higher (all P<0.05); while a significant difference was only found in naïve CD4 T cells (P<0.05). HLA-DR expression was increased significantly in all CD4 and CD8 T cell subsets. Both naïve (CD45RA+) and memory (CD45RO+) CD8 T cells in this population had significantly shorter telomere lengths (P<0.01) compared to the HC group. Conclusion: HIV-infected MSM exhibit signs of accelerated immune senescence and biological aging, which particularly affects the CD8 T-cell subsets.
Keywords: HIV infections